Learning Analytics - Erik Duval; Katrien Verbert (FernUniversität Hagen, 2012)
This paper provides a brief introduction to the domain of 'learning analytics'. We first explain the background and idea behind the concept. Then we give a brief overview of current research issues. We briefly list some more controversial issues before concluding.